Persatuan Pembangunan Party in Nanggroe Aceh Darussalam Province 1973-1998 - Alfian Alfian; Suprayitno Suprayitno; Warjio Warjio (Budapest International Research and Critics University, 2019)
After the establishment of PPP in the provincial area which is explained in the previous section, it was immediately based on instructions from the center to establish DPC-DPC in Daerah Istimewa Aceh Province. The establishment of the Branch Board (DPC) began in 1974. This article uses a theoretical and approach approach in pilitik science. For research methods, this study uses historical methods. This article explains how PPP can exist or survive in the face of government party hegemony namely Golkar. In this research, the campaign system, election results, PPP vision and party goals are also described.